Analysis on the aesthetics through pattern and motif of bamboo in Malays architecture / Mariam Idris ... [et al.] - Idris, Mariam; Abdullah, Hajah Fadilah; Md Hashim, Azhari (2014)
Malay bamboo architecture can be seen in most of the Northern part of Malaysia. The beauty of these bamboo plants brings a sense of naturality to the environment. Thus, the esthetic values from bamboo is still continued and appreciated days in Malay architecture. This research aims to nurture awareness to the community in preserving the Malay’s architectural heritage. Furthermore, its aesthetical value helps architects, interior designers and art students in expanding their creativity for their benefits. Bamboo aesthetic beauty will be able to attract tourists to learn and appreciate Malay’s art. Bamboo is an environmental friendly plant which is suitable for architecture. The Malay’s aesthetic value in bamboo has not been highlighted since it involves hard work in handling it. The process of handling the raw bamboos has always been in a traditional way which is quite a challenge and also the raw bamboos are not durable for long time. These short comings explain the in popularity of bamboos in modern Malay architecture. This research is a qualitative research in which it encompasses the concept of descriptive design. This concept denotes a documental photography towards the situations and also the materials. The objective of this research focuses on analyzing the application of bamboos in Malay architecture. Secondly the objective is to identify the various patterns and shapes created through arrangement and weave composition by using bamboo. Lastly to conclude the aesthetic values depicted from nature through the usage of bamboo in Malay architecture.